IPO Post-Issue Markets: Questionable Predilections But Diligent Learners? - Bossaerts, Peter; Hillion, Pierre (The Review of Economics and Statistics, 2001)
There appear to be no anomalies in the aftermarket of a sample of 4,848 U.S. IPOs over the period 1975 to 1995, except issues offered below $6. Risk is priced in the aftermarket in accordance with Rubin-stein's asset-pricing model. Unlike under the efficient markets hypothesis (EMH), however, market priors about the probability of future default are not unbiased at the IPO date. Still, subsequent learning is rational: the market uses Bayes' law with a correct-likelihood function (of news given the eventual fate of an issue). That is, the hypothesis of an efficiently learning market (ELM) cannot be rejected. We produce direct evidence in support of these statements, based on a new class of tests. We also provide indirect evidence, by documenting a gradual convergence of IPO prices towards EMH as issues mature.